Incidental finding of bronchial diverticula in a non-smoker population: evaluation on thin-section CT - Ciccarese, Federica; Garzillo, Giorgio; Chiesa, Anna Maria; Poerio, Antonio; Baroncini, Serena; Bacchi Reggiano, Maria Letizia; Sverzellati, Nicola; Zompatori, Maurizio (Monaldi Archives for Chest Disease, 2016)
Bronchial diverticula have been described as a common radiological finding in smoker patients with COPD, but the specificity of this sign should be further investigated. Thus, the aim of our study was to evaluate the prevalence of diverticula in a cohort of non-smoker subjects. Between February and July 2012, 2438 patients were admitted to our Radiology Unit to undergo a chest CT. Among them, we enrolled 121 non-smoking patients (78/121-64.5% females, 43/121-35.5% males), of different age (57.0Â±20.7 years-range: 12-88), without any respiratory symptoms, submitted to chest CT for several reasons (oncologic evaluation: 59/121-48.8%; follow up of lung nodules: 27/121-22.3%; screening in connectivitis: 12/121-9.9%; others: 23/121-19.0%). We considered thin-section CT scan on axial, coronal and sagittal plans to evaluate prevalence, numbers and level of bronchial diverticula. Diverticula were found in 41/121-33.9% patients, with a slight major prevalence in males (p=0.048), but no significant difference on age. In 31/41-75.6% the number was <3, whereof 17/31-54.8% with just one diverticulum assessed. Regarding the level, in 30/41-73.2% they were subcarinal, but they were also detected in mainstem (2/41-4.9%) and lobar bronchi (with the right upper lobe bronchus most frequently involved- 12/41-29.3%). Bronchial diverticula can be observed in non-smokers, as well as in smoker patients with COPD. However, their prevalence seems to be lower than in smokers and they tend to be isolated and subcarinal. The age of patients does not influence their finding. More studies should be proposed to better define a cut-off between smokers and healthy subjects.